The Relationship Between Technological Self-Efficacy and Organizational Citizenship Behavior During Covid-19: Analyzing the Moderating Role of Trust - Torrance, Christopher G.; Lundy, Baruch; Day, Steven W.; Lundy, Harold W. (Journal of Applied Business and Economics, 2023)
In this study, we examine the intricate relationship between technological self-efficacy, organizational citizenship behavior (OCB), and the moderating influence of trust—a facet largely unexplored in existing literature. The COVID-19 pandemic has intensified the reliance on technologies like Zoom and Microsoft Teams, creating a unique backdrop. Amid the elevated anxiety surrounding the adoption of "new" technology, we hypothesize that trust within the workplace will play a pivotal role in moderating the link between technological self-efficacy and OCB. Our research aims to shed light on this uncharted territory, offering insights into how trust shapes employees' responses to technological challenges, particularly in the context of a global crisis.